2020
DOI: 10.1021/acs.nanolett.0c03704
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Electronic Structure of an α-Antimonene Monolayer through Interface Engineering

Abstract: The interfacial charge transfer from the substrate may influence the electronic structure of the epitaxial van der Waals (vdW) monolayers and thus their further technological applications. For instance, the freestanding Sb monolayer in puckered honeycomb phase (α-antimonene), the structural analog of black phosphorene, was predicted to be a semiconductor, but the epitaxial one behaves as a gapless semimetal when grown on the T d -WTe 2 substrate. Here, we demonstrate that interface engineering can be applied t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 57 publications
2
22
0
1
Order By: Relevance
“…15−21 Freestanding β-Sb is essentially a monolayer of Sb(111) and predicted to undergo a thickness-dependent transition from a normal semiconductor to a topological insulator to a topological semimetal with increasing thickness. 17,18,22 Meanwhile, α-Sb, the antimony analogue of black phosphorene (BP), 23 was reported to exhibit high carrier mobility and tunable electronic structures through substrates, 24,25 which is highly desirable for electronic and optoelectronic applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15−21 Freestanding β-Sb is essentially a monolayer of Sb(111) and predicted to undergo a thickness-dependent transition from a normal semiconductor to a topological insulator to a topological semimetal with increasing thickness. 17,18,22 Meanwhile, α-Sb, the antimony analogue of black phosphorene (BP), 23 was reported to exhibit high carrier mobility and tunable electronic structures through substrates, 24,25 which is highly desirable for electronic and optoelectronic applications.…”
Section: Introductionmentioning
confidence: 99%
“…30,31 The synthesis of α-Sb has been achieved on Bi thin films, 32 WTe 2 , 25 MoTe 2 , and SnSe substrates. 24 Recently, Hogan and co-workers reported that α-Sb prepared on Bi 2 Se 3 can undergo a phase transition to β-Sb by gentle annealing. 33 Meanwhile, Shi et al showed that the distorted hexagonal-like Sb lattice formed on the SnSe substrate at the initial stage will eventually transform into the energetically favorable α-Sb.…”
Section: Introductionmentioning
confidence: 99%
“…The success of mechanically exfoliated graphene has sparked blowout research interests in two‐dimensional (2D) van der Waals (vdW) materials, [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ] with substantial attention paid to the graphene family, [ 2 , 3 , 4 , 5 , 6 , 7 ] transition metal dichalcogenides (TMDs), [ 8 , 9 , 10 ] 2D metal carbides/nitrides (MXenes), [ 11 , 12 , 13 , 14 , 15 , 16 ] and black phosphorene. [ 17 , 18 , 19 , 20 , 21 ] In contrast to the bulk counterparts, these materials at the 2D limit exhibit a diverse range of intriguing properties.…”
Section: Introductionmentioning
confidence: 99%
“…In analogy to other elemental 2D materials, phase engineering can be realized via delicately tuning the substrate temperature and using appropriate substrates. Black-phosphorus like antimonene can be stabilized on Bi 2 Se 3 after room temperature (RT) deposition, and transforms to blue-phosphorus like phase after annealing at 473 K due to the perfect lattice match . The phase transition of 2D materials from puckered to buckled phase has shown to be a general trend via bond breaking pathway when taking into the substrate into account.…”
Section: Resultsmentioning
confidence: 99%